Scorpion-Centipede extracts mitigate ovariectomy-induced osteoporosis in mice through facilitating Cx3cr1 expression - Ni, Jinghuai; Yu, Lingling; Wang, Bingjie; Chen, Shuai; Shang, Wenbin; Fang, Penghua; Du, Bin; Min, Wen (Frontiers in Pharmacology, 2025)
ObjectivesScorpion and Centipede (SC) is an ancient formula of traditional Chinese medicine that is commonly utilized in a range of disorders, and it has been shown to have pharmacological effects on postmenopausal osteoporosis (PMOP). However, the specific mechanism of SC for the treatment of PMOP remains to be further investigated. This study aimed to investigate the therapeutic potential of a traditional Chinese medicine formula consisting of SC in regulating the osteogenic and adipogenic differentiation of bone marrow mesenchymal stem cells (BMMSCs) to treat PMOP.MethodsThe ovariectomy-induced mice (OVX) were established and divided into a sham surgery group, OVX, OVX with alendronate sodium, and OVX with SC, and kept for 10 weeks. In vitro experiments were conducted to evaluate the effects of SC on osteogenic and adipogenic differentiation in BMMSCs, MC3T3-E1, and 3T3-L1 cells.ResultsThe results showed that SC treatment significantly improved bone mineral density (BMD), trabecular separation (Tb.Sp), trabecular thickness (Tb.Th), trabecular number (Tb.N), bone volume fraction (BV/TV), and trabecular pattern factor (Tb.Pf) in OVX mice. In addition, SC treatment markedly increased Runx2, Osx, Alp, and Cx3cr1 while decreasing adipogenic genes like PPARγ and C/EBPα in the bone tissue of OVX mice and BMMSCs. Notably, the effects of SC on osteogenic and adipogenic genes were blocked in Cx3cr1 knockdown MC3T3-E1 and 3T3-L1 cells.ConclusionThis study demonstrates that the SC effectively increases bone mass and osteogenesis by promoting Cx3cr1, thereby increasing osteogenic differentiation and inhibiting adipogenic differentiation. These findings amplified the mechanisms of SC and its potential to treat PMOP.